Keterlibatan Artificial Intelligence sebagai Katalisator Perancangan Putusan Perkara Perdata di Indonesia - Alexandro Wiranto Tambe; Amiradiaty Nasution; Nabila Fitria Almadea (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
AI has been widely used in various nations, especially in the economy, healthcare, and law. However, its current state is limited to weak AI, lacking full awareness and control. Some countries use AI to assist legal professionals in analyzing legal documents and in helping judges with research during court proceedings. Thus, exploring AI's role and regulation in making civil case decisions within Indonesian law is crucial. This study relies on secondary data and normative legal methods. Findings suggest weak AI is promising for crafting judgments in Indonesian civil cases due to its focus on formal truth. Implementing regulations, possibly Supreme Court Regulations (PERMA), is necessary for the possible use of AI in Indonesia's court proceedings. These rules should define, classify, and limit AI, ensuring legal reliability in its application.